Emerging perspectives in big data warehousing - Taniar, David 1963-; Rahayu, Johanna Wenny 1963- (IGI Global, 2019)
"This book disseminates the latest research findings in the areas of data management and analyzation. It also focuses on the integration between the fields of data warehousing and data mining"--
Keywords: Data warehousing; Data mining; Big data